2022
DOI: 10.1017/s0950268822000334
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing SARS-CoV-2 infection rate in Belgian nursing home residents during the first wave of COVID-19 pandemic

Abstract: In April 2020, Belgium experienced high numbers of fatal COVID-19 cases among nursing home (NH) residents. In response, a mass testing campaign was organised testing all NH residents and staff. We analysed data of Flemish NH to identify institutional factors associated with increased SARS-CoV-2 infection rates among NH residents. Cross-sectional study was conducted between April 8-May 15, 2020. Data collected included demographics, group category (i.e. staff or resident), symptom status and test result. We ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…A large-scale regional study in Belgium showed that higher infection rates among residents were linked to an increased infection rate among nursing home staff members and a higher fraction of beds for individuals who were heavily dependent. However, no association with the size or type of nursing home, mean age of residents/staff or the proportion of asymptomatic positive tested cases was found [ 25 ]. Other large-scale studies, conducted in the United States, Scotland and Canada did not find such associations [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large-scale regional study in Belgium showed that higher infection rates among residents were linked to an increased infection rate among nursing home staff members and a higher fraction of beds for individuals who were heavily dependent. However, no association with the size or type of nursing home, mean age of residents/staff or the proportion of asymptomatic positive tested cases was found [ 25 ]. Other large-scale studies, conducted in the United States, Scotland and Canada did not find such associations [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other large-scale studies, conducted in the United States, Scotland and Canada did not find such associations [ 26 , 27 , 28 ]. Since the provision and organizational structure of the nursing home setting can vary between countries and regions, comparing them with other geographical regions is challenging [ 1 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The individual factors that were most supported by the body of evidence with relation to COVID-19 outbreak include age [24,39,46,60,63,97,101,105,115], dependency level [22,46,54,58,63,72,101,105], frailty [24,58,115], sex (female) [45,56,91], and cognitive deterioration/dementia [105,107,115].…”
Section: Individual Factors Related To Outbreaksmentioning
confidence: 99%
“…Staff is an associated risk factor due to regular external contacts [ 12 , 13 ], which is moderated by the registered nurses’ ratio and number of staff members [ 5 , 14 , 15 ] and has been associated with fewer deaths by COVID-19 when there is a higher registered nurses’ ratio [ 14 , 16 ]. In Germany, a registered nurses’ ratio of 50% for qualified personnel is mandated; however, not all facilities are able to meet this requirement due to a shortage of skilled staff.…”
Section: Introductionmentioning
confidence: 99%